Reviews - Kabi Hartman; Caleb Corkery; Joel Kline; Terri Pullen Guezzar (Journal of the Assembly for Expanded Perspectives on Learning, 2007)
Reviews Kabi Hartman. Writing With, Through and Beyond the Text: An Ecology of Language. (Rebecca Luce-Kapler, 2004) Caleb Corkery. African American Literacies Unleashed: Vernacular English and the Composition Classroom. (Arnetha F. Ball and Ted Lardner, 2005) Joel Kline . Race, Rhetoric, and Technology: Searching for Higher Ground. (Adam J. Banks, 2006) Terri Pullen Guezzar. Why Is Corporate America Bashing Our Public Schools? (Kathy Emery and Susan Ohanian, 2004)